Enhancing elementary teacher competence through Love-based Curriculum, deep learning, and AI via Action Research - Risnawati; Zubaidah Amir MZ; Mimi Hariyani; Dicki Hartanto; M. Fikri Hamdani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
This community service program aims to enhance the competencies of elementary school teachers (SD/MI) in Pekanbaru City in integrating a Love-based Curriculum, deep learning approaches, and the utilization of Artificial Intelligence (AI) in classroom instruction. The program was implemented through several stages, including needs analysis, training (knowledge transfer), mentoring, classroom implementation, and evaluation and reflection. The training focused on strengthening teachers’ understanding and practical skills in designing learning tools that integrate values-based education, deep learning strategies, and AI applications such as ChatGPT and Canva AI. The results indicate a significant improvement in teachers’ competencies, as reflected in the increased quality of instructional materials, the ability to integrate values and technology into teaching practices, and the contextual use of AI in lesson planning. Furthermore, classroom implementation demonstrates a positive impact on the learning process, including increased student engagement, more interactive classroom communication, and a more reflective and supportive learning environment. Therefore, this community service program not only improves teachers’ competencies but also contributes to enhancing the overall quality of classroom learning through the holistic integration of values, pedagogy, and technology.